Defective AMPK regulation of cholesterol metabolism accelerates atherosclerosis by promoting HSPC mobilization and myelopoiesis - Man K.S. Lee; Olivia D. Cooney; Xuzhu Lin; Shaktypreya Nadarajah; Dragana Dragoljevic; Kevin Huynh; Danise-Ann Onda; Sandra Galic; Peter J. Meikle; Thomas Edlund; Morgan D. Fullerton; Bruce E. Kemp; et al. (Elsevier, 2022)
Objectives: Dysregulation of cholesterol metabolism in the liver and hematopoietic stem and progenitor cells (HSPCs) promotes atherosclerosis development. Previously, it has been shown that HMG-CoA-Reductase (HMGCR), the rate-limiting enzyme in the mevalonate pathway, can be phosphorylated and inactivated by the metabolic stress sensor AMP-activated protein kinase (AMPK). However, the physiological significance of AMPK regulation of HMGCR to atherogenesis has yet to be elucidated. The aim of this study was to determine the role of AMPK/HMGCR axis in the development of atherosclerosis. Methods: We have generated a novel atherosclerotic-prone mouse model with defects in the AMPK regulation of HMGCR (Apoe−/−/Hmgcr KI mice). Atherosclerotic lesion size, plaque composition, immune cell and lipid profiles were assessed in Apoe−/− and Apoe−/−/Hmgcr KI mice. Results: In this study, we showed that both male and female atherosclerotic-prone mice with a disruption of HMGCR regulation by AMPK (Apoe−/−/Hmgcr KI mice) display increased aortic lesion size concomitant with an increase in plaque-associated macrophages and lipid accumulation. Consistent with this, Apoe−/−/Hmgcr KI mice exhibited an increase in total circulating cholesterol and atherogenic monocytes, Ly6-Chi subset. Mechanistically, increased circulating atherogenic monocytes in Apoe−/−/Hmgcr KI mice was associated with enhanced egress of bone marrow HSPCs and extramedullary myelopoiesis, driven by a combination of elevated circulating 27-hydroxycholesterol and intracellular cholesterol in HSPCs. Conclusions: Our results uncovered a novel signalling pathway involving AMPK-HMGCR axis in the regulation of cholesterol homeostasis in HSPCs, and that inhibition of this regulatory mechanism accelerates the development and progression of atherosclerosis. These findings provide a molecular basis to support the use of AMPK activators that currently undergoing Phase II clinical trial such as O-3O4 and PXL 770 for reducing atherosclerotic cardiovascular disease risks.